Development of an ecosystem model for post-mining land use with a systems dynamics approach - Hesketh, P; Zevallos, M; Chichakly, K (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Returning mined land at closure to its pre-mining land use is not always desired or possible due to alterations of the landscape and socio-economic context. Post-mining land use (PMLU) is often promoted as a solution, however, significant effort is required in developing PMLU options with different land uses providing widely different outputs. The mine site can be a value driver by providing resources (e.g. water, waste and land) that can springboard these activities. A holistic approach to understanding the whole business ecosystem and the interrelationships between different PMLU activities and how these activities reinforce each other (generation of wastes, supply of energy, use of water and benefits developed) thus supports a sustaining system. This constitutes a complex and dynamic system that can be represented and modelled through system dynamics theory. It is how a change in one variable affects other variables over time through a series of feedback loops. In relation to PMLU, an example of this behaviour is the interrelationship between land, cropping for energy generation, irrigation of the crop with mine water and the impact on biomass generated, and economic activity developed (measured as jobs). This paper describes the development of an ecosystem model which provides a dynamic tool capable of: integrating extensive amounts of information to simulate a range of processes and interactions across a number of value streams over the life of an asset identifying flow optimisation pathways and opportunities/solutions that seek to eliminate waste and pollution, circulate products and materials, and regenerate land identifying major gaps in knowledge so that actions can be implemented to close these improving the understanding of the whole business ecosystem including major processes, drivers and responses simulating alternative options in a simple visual way to inform decision-making around PMLU supporting investment decisions.
Keywords: post-mining land use